MENINGKATKAN PEMBELAJARAN PASSING BOLAVOLI DENGAN MEDIA KERANJANG TARGET (Department of Physical Education, Sport, Health and Recreation, 2013)
The problems of the study is whether the target basket to improve learning outcomes of students passing gradevolleyball at SMP Negeri 1 Balapulang?. This study aims to determine the basic engineering efforts to enhancelearning with media basket volleyball targets on class VII in learning Penjasorkes. This research method isclassroom action research refers to the increase in learning through the medium of the target basket that hasbeen modified. The subjects in this study were students of class VII F Junior High School 1 Balapulang the 36students consisting of men and women amounted to 15 students totaling 21 students. The study was conductedin two cycles of action. I cycle research results, obtained an average grade 69.63 with 56% percentage of masterylearning. Second cycle of research results, obtained an average grade 77.31 with 81% percentage of masterylearning. From the results obtained it can be concluded that the learning targets volleyball cart with mediamanaged to improve students' skills in supporting the process of learning the basic techniques of volleyball inthe seventh grade students of Junior High School 1 F Balapulang. So the authors provide suggestions:Application of the target media basket on learning the basic techniques of volleyball as products that haveresulted from this research can be used as an alternative in learning the basic techniques of volleyball instudents.